A real-world disproportionality analysis of mesalazine data mining of the public version of FDA adverse event reporting system - Liu, Mingdi; Gu, Liting; Zhang, Yuning; Zhou, Honglan; Wang, Yishu; Xu, Zhi-Xiang (Frontiers in Pharmacology, 2024)
Background: Mesalazine, a preparation of 5-aminosalicylic acid, is a medication widely used in clinical practice as a first-line therapy in the treatment of mild and moderate inflammatory bowel disease. However, the long-term safety of mesalazine in large sample population was unknown. The current study was to assess mesalazine -related adverse events (AEs) of real-world through data mining of the US Food and Drug Administration Adverse Event Reporting System (FAERS).Methods: Disproportionality analyses, including the reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN) and the multiitem gamma Poisson shrinker (MGPS) algorithms were employed to quantify the signals of mesalazine -associated AEs.Results: Out of 14149980 reports collected from the FAERS database, 24284 reports of mesalazineassociated AEs were identified. A total of 170 significant disproportionality preferred terms (PTs) conforming to the four algorithms simultaneously were retained. The most common AEs included colitis ulcerative, diarrhoea, condition aggravated, crohn's disease, fatigue, abdominal pain, nausea, haematochezia, which were corresponding to those reported in the specification and clinical trials. Unexpected significant AEs as dizziness, drug ineffective, drug hypersensitivity, infection, off label use, weight decreased, decreased appetite, arthralgia, rash might also occur. The median onset time of mesalazine -related AEs was 1127 days (interquartile range [IQR] 1127-1674 days), and most of the cases occurred occurred 2 years later (n=610, 70.93%) and within the first 1month (n=89, 10.35%) after mesalazine initiation.Results of our study were consistent with clinical observations. We also found potential new and unexpected AEs signals for mesalazine, suggesting prospective clinical studies were needed to confirm these results and illustrate their relationship. Our results could provide valuable evidence for further safety studies of mesalazine.